Design of Automatic Water Tank Cleaning Machine using Catia Software: Efficient and Chemical-Free Cleaning of Cylindrical Water Tanks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this modern world, cleaning of overhead tanks manually is a tedious job. It is observe that the cleaning of cylindrical tank is sometime difficult and peoples hesitate to clean although it’s dirty. Clean water supply is important in ensuring good health of people. Water supply is distributed from water storage tanks. Sediment that accumulates over time in water storage tanks will deteriorate the water quality used by consumers. Purpose of this project is to clean domestic cylindrical water tank with the help of mechanical system consists of motor, brush, rack and pinion, lead screw etc. The rack and pinion arrangement is used to move whole mechanical system up and down for cleaning of cylindrical tank. Our aim behind this project is to reduce the human efforts and to avoid the chemical influence on health of person entering the tank for cleaning. We assemble the system so that there will be no need of human interaction while cleaning the tank.